Maths for chemists - Cockett, Martin (Tutorial chemistry texts, 2012)
The two volumes of Maths for Chemists provide an excellent resource for all undergraduate chemistry students but are particularly focussed on the needs of students who may not have studied mathematics beyond GCSE level (or equivalent). The texts are introductory in nature and adopt a sympathetic approach for students who need support and understanding in working with the diverse mathematical tools required in a typical chemistry degree course. Maths for Chemists Volume II: Power Series, Complex Numbers and Linear Algebra builds on the foundations laid in Volume I, and goes on to develop more a.